2018
DOI: 10.1186/s40644-018-0141-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary carcinosarcoma of the liver: imaging features and clinical findings in six cases and a review of the literature

Abstract: BackgroundCarcinosarcoma of the liver is a very rare tumor composed of a mixture of carcinomatous and sarcomatous elements. Less than 25 adequately documented cases have been reported, with inadequate description of imaging features. In order to improve the awareness of this rare tumor, this study aimed to analyze the clinicopathologic and imaging features of six cases of hepatic carcinosarcoma (HCS) confirmed by surgical pathologic evaluation.MethodsWe retrospectively studied the clinicopathologic and imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 20 publications
0
34
0
9
Order By: Relevance
“…Although sarcomatoid carcinoma and carcinosarcoma are synonymously used, sarcomatoid carcinoma is preferred for spindle cells with remaining epithelial differentiation confirmed through immunohistochemical staining‐positive epithelial markers, such as CK, and no specific type of mesenchymal lineage, whereas carcinosarcoma is preferred for spindle cells with specific mesenchymal differentiation . On the basis of the fourth edition of the WHO classification of tumors, carcinosarcoma is currently understood as a carcinoma that has undergone sarcoma‐like differentiation . Similar to sarcomatoid carcinoma, the sarcomatoid component of carcinosarcoma is considered to be a clonal evolution of the differentiated component (HCC or cholangiocarcinoma) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sarcomatoid carcinoma and carcinosarcoma are synonymously used, sarcomatoid carcinoma is preferred for spindle cells with remaining epithelial differentiation confirmed through immunohistochemical staining‐positive epithelial markers, such as CK, and no specific type of mesenchymal lineage, whereas carcinosarcoma is preferred for spindle cells with specific mesenchymal differentiation . On the basis of the fourth edition of the WHO classification of tumors, carcinosarcoma is currently understood as a carcinoma that has undergone sarcoma‐like differentiation . Similar to sarcomatoid carcinoma, the sarcomatoid component of carcinosarcoma is considered to be a clonal evolution of the differentiated component (HCC or cholangiocarcinoma) .…”
Section: Discussionmentioning
confidence: 99%
“…(27) On the basis of the fourth edition of the WHO classification of tumors, carcinosarcoma is currently understood as a carcinoma that has undergone sarcoma-like differentiation. (28,29) Similar to sarcomatoid carcinoma, the sarcomatoid component of carcinosarcoma is considered to be a clonal evolution of the differentiated component (HCC or cholangiocarcinoma). (10,30) Additionally, in a comparative study between sarcomatoid carcinoma and carcinosarcoma, no significant difference was noted between these two types of biphasic tumors for several clinicopathological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,8 Due to its rarity, there have been limited data regarding the outcomes of patients with sarcomatoid HCC, with those few studies focusing on the radiologic or histopathologic features of the disease. [9][10][11][12] For example, although Jernigan et al reported on 20 cases of patients with sarcomatoid HCC, the sample size was too small to assess the long-term outcomes of these patients compared with individuals with conventional HCC. 13 As such, the objective of the current study was to provide a comprehensive assessment of the incidence, treatment, and prognosis of patients with sarcomatoid HCC identified in the National Cancer Data Base (NCDB).…”
Section: Introductionmentioning
confidence: 99%
“…Previous published papers mostly reviewed the pathogenesis and clinical characteristics [2][3][4][5] or described the imaging features in computed tomography (CT), magnetic resonance imaging (MRI) or 18 F-fluorodeoxyglucose positron emission tomography (PET) of PHCS [6][7][8]. Little is known about ultrasound (US) and contrast-enhanced ultrasound (CEUS) [9].…”
Section: Introductionmentioning
confidence: 99%